2007
DOI: 10.1111/j.1600-0463.2007.apm_656.x
|View full text |Cite
|
Sign up to set email alerts
|

Claudins 1, 3, 4, 5 and 7 in esophageal cancer: loss of claudin 3 and 4 expression is associated with metastatic behavior

Abstract: The aim of the study was to elucidate the significance of claudins in surgically treated esophageal carcinoma. The expression of claudins 1, 3, 4, 5 and 7 was studied by immunohistochemistry. Tumor proliferation was assessed with Ki67 immunostaining and apoptosis by the TUNEL method and immunostaining of fragmented caspase 3. Adenocarcinomas showed significantly more cases with moderate or strong claudin 3 (p<0.001) and claudin 5 positivity (p=0.031) compared to squamous cell carcinomas. Loss of claudin 3 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 39 publications
2
32
2
4
Order By: Relevance
“…21,22 However, a study conducted in patients with surgically treated esophageal carcinomas has found that loss of claudins 3 and 4 expression was associated with the presence of distant metastases, 23 indicating again that claudin isoforms indeed may have a highly tissue specific role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, a study conducted in patients with surgically treated esophageal carcinomas has found that loss of claudins 3 and 4 expression was associated with the presence of distant metastases, 23 indicating again that claudin isoforms indeed may have a highly tissue specific role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a tendency to reduced the claudin-1 expression in the cases with venous clarified in the esophagus extensively. In addition, only several studies examined claudins expression in the esophageal diseases including cancers (6,13,15,23,28). In this study, we demonstrated that decreased expression of claudin-1 was correlated with the recurrence status in esophageal squamous cell carcinoma, and associated with short disease-free survival and overall survival.…”
Section: Evaluation Of Immunostaining Patterns Of Claudin-1mentioning
confidence: 61%
“…Recently, two different studies have been reported; one report described that significant association was not detected between the claudin-1 expression and clinicopathological factors except for histological differentiation of the tumor (28), and another study reported that the claudin-1 expression was not associated with clinicopathological features including tumor grade, tumor size, T-stage, presence of lymph nodal and distal metastases (23). The discrepancies between our results and these studies are thought to result from the methods for the evaluation of immunoreactivities.…”
Section: Evaluation Of Immunostaining Patterns Of Claudin-1mentioning
confidence: 99%
See 2 more Smart Citations